Perancangan Sistem Absensi Dan Nilai Siswa Berbasis Web Menggunakan Metode Waterfall Pada SMP Swasta Brigjend Katamso 2 Medan - Dea Monica Putri; Hendry; Afif Badawi (Jurnal Nasional Teknologi Komputer, 2026)
In a school environment, managing student academic data, such as attendance and grades, is a vital component that requires high accuracy and efficiency. This data serves not only as an administrative record but also as a basis for evaluating student and school performance. At Brigjend Katamso 2 Middle School in Medan, attendance and grade management still uses manual methods, which can lead to errors and delays. This research uses the Waterfall method to create a prototype system design that can present web-based student attendance and grade data quickly and accurately, and facilitate more efficient reporting for the school. The Waterfall method was chosen because of its systematic and sequential approach, ensuring each development stage (analysis, design, implementation, testing) is completed thoroughly and in a structured manner, resulting in a robust system that meets the school's specific needs. The results of this research are expected to provide a description of the information system development process using the Waterfall method.